2015
DOI: 10.1111/nmo.12558
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of small bowel motility in patients with Crohn's disease using dynamic MRI

Abstract: Quantitative assessment of motility alterations by means of motility scoring in small bowel segments affected by CD provides additional information on inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…MRI is non‐invasive, safe and widely available and, coupled with advances in post‐processing technologies, enables rapid and repeatable quantification . Encouragingly, the first steps toward clinical implementation have been taken with dynamic motility imaging now being routine in various centers and with several prospective clinical studies being published …”
Section: Introductionmentioning
confidence: 99%
“…MRI is non‐invasive, safe and widely available and, coupled with advances in post‐processing technologies, enables rapid and repeatable quantification . Encouragingly, the first steps toward clinical implementation have been taken with dynamic motility imaging now being routine in various centers and with several prospective clinical studies being published …”
Section: Introductionmentioning
confidence: 99%
“…motility using MRI is providing novel insights into CD pathophysiology. [9][10][11][12][13][14] Indeed, recent single-site data in 53 patients suggests that aberrant motility (notably a decreased variability) in apparently healthy bowel may be linked to patient symptom burden in CD. 15 If this observation could be prospectively validated, MRI quantified bowel motility could provide new insights into the aetiology of abdominal symptoms in CD, act as a target for therapeutic monitoring and possibly aid drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that small bowel motility quantified with dynamic MRI can be used as a biomarker of inflammatory activity in Crohn's disease and to differentiate healthy from diseased bowel . The motility in the terminal ileum was lower in Crohn's patients in comparison to healthy subjects .…”
Section: Clinical Implementationmentioning
confidence: 99%
“…The short observation periods associated with breath-hold protocols may seem inadequate to measure GI motility, but have shown good initial results 4,10,16,[20][21][22][23][24][25][26] and are very practical for clinical use. Recent work showed that in breath-hold scanning, using a displacement mapping quantification technique (described below), a temporal resolution of at least 1 image per second and duration of 15 seconds is required for robust assessment of motility.…”
Section: Image Acquisitionmentioning
confidence: 99%